Cassava: Biology, Production and Utilization 2001
DOI: 10.1079/9780851995243.0281
|View full text |Cite
|
Sign up to set email alerts
|

Cassava utilization, storage and small-scale processing.

Abstract: This paper considers world cassava utilization and the nutritional value of the root and leaves for human consumption. The current state of knowledge on cassava storage and small-scale processing is presented with emphasis on sub-Saharan Africa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
140
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(151 citation statements)
references
References 25 publications
4
140
0
Order By: Relevance
“…The crop is one of the most important staple food with about 93% of the production used for human consumption (Nweke, Spencer, & Lynam, 2002). The roots of this important carbohydrate source are eaten both fresh and as processed products (Westby, 2002). However, in its tissue, cassava contains cyanogenic glycosides, mainly linamarin, that are enzymatically hydrolysed to glucose, acetone and hydrogen cyanide during cell rupture (Conn, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The crop is one of the most important staple food with about 93% of the production used for human consumption (Nweke, Spencer, & Lynam, 2002). The roots of this important carbohydrate source are eaten both fresh and as processed products (Westby, 2002). However, in its tissue, cassava contains cyanogenic glycosides, mainly linamarin, that are enzymatically hydrolysed to glucose, acetone and hydrogen cyanide during cell rupture (Conn, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Processing cassava into flour is a value addition for expanding the range of uses of the root crop. The flour has been applied as a raw material for ethanol and other fermented foods [9,10] and has partially replaced wheat flour for food and plywood industries [5,[11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Reports have shown that age, variety and environmental conditions influence the occurrence and concentration of hydrogen cyanide in various parts of the cassava plant and at different stages of development respectively (Albert et al, 2005). This means that some varieties generally considered sweet (low cyanide content) can have a high cyanogenic potential under certain conditions (Westby, 2002). Bokanga et al (1994) reported that total cyanide levels in roots increase in a year of low rainfall or drought due to water stress on the plant.…”
Section: Hydrogen Cyanidementioning
confidence: 99%